By definition, the average change of rate is given by:
[tex]AVR = \frac{f(x2)-f(x1)}{x2-x1} [/tex]
We will calculate AVR for each of the functions.
We have then:
f(x) = x^2 + 3x interval: [-2, 3]:
[tex]f(-2) = x^2 + 3x = (-2)^2 + 3(-2) = 4 - 6 = -2
f(3) = x^2 + 3x = (3)^2 + 3(3) = 9 + 9 = 18 [/tex]
[tex]AVR = \frac{-2-18}{-2-3} [/tex]
[tex]AVR = \frac{-20}{-5} [/tex]
[tex]AVR = 4 [/tex]
f(x) = 3x - 8 interval: [4, 5]:
[tex]f(4) = 3(4) - 8 = 12 - 8 = 4 f(5) = 3(5) - 8 = 15 - 8 = 7[/tex]
[tex]AVR = \frac{7-4}{5-4} [/tex]
[tex]AVR = \frac{3}{1} [/tex]
[tex]AVR = 3 [/tex]
f(x) = x^2 - 2x interval: [-3, 4]
[tex]f(-3) = (-3)^2 - 2(-3) = 9 + 6 = 15
f(4) = (4)^2 - 2(4) = 16 - 8 = 8[/tex]
[tex]AVR = \frac{8-15}{4+3} [/tex]
[tex]AVR = \frac{-7}{7} [/tex]
[tex]AVR = -1 [/tex]
f(x) = x^2 - 5 interval: [-1, 1]
[tex]f(-1) = (-1)^2 - 5 = 1 - 5 = -4
f(1) = (1)^2 - 5 = 1 - 5 = -4[/tex]
[tex]AVR = \frac{-4+4}{1+1} [/tex]
[tex]AVR = \frac{0}{2} [/tex]
[tex]AVR = 0 [/tex]
Answer:
these functions from the greatest to the least value based on the average rate of change are:
f(x) = x^2 + 3x
f(x) = 3x - 8
f(x) = x^2 - 5
f(x) = x^2 - 2x